Excellent high-temperature dielectric energy storage performance in bilayer nanocomposites with high-entropy ferroelectric oxide fillers - Xuan Zhao; Lei Zhang; Zhenhao Fan; Yuyan Huang; Yongming Hu; Meng Shen; Zhao Wang; Yunbin He; Dawei Wang; Qingfeng Zhang (Nature Communications)
Abstract The low dielectric constant, limited breakdown strength, and large polarization hysteresis and conduction loss constrain discharged energy density and efficiency of polymer-based dielectric capacitors at elevated temperatures. To address these challenges, the [0.8(Na0.2Bi0.2Ba0.2Sr0.20Ca0.2)TiO3-0.2NaNbO3]@Al2O3 high-entropy ferroelectric nanoparticles/polyetherimide-AlN/polyetherimide-triptycene bilayer nanocomposites are designed. The bilayer nanocomposites capitalize on advantages of high-entropy ferroelectric fillers, which contribute to the high dielectric constant and minimal hysteresis at high temperatures. Additionally, they also benefit from high thermal conductivity of AlN, enhanced rigidity and charge carrier traps in polyetherimide-triptycene, and suppressed carrier transport at the bilayer film interfaces. Consequently, the bilayer nanocomposites exhibit significantly improved dielectric constant and breakdown strength, and marked reduction in conduction loss at elevated temperatures. Remarkably, a record-high discharged energy density of 12.35 J cm−3 is achieved in the optimized bilayer nanocomposites at 150 °C, accompanied by a large efficiency of 90.25% under an electric field of 6341 kV cm−1.